Crystallography of Interfaces and Grain Size Distributions in Sr‐Doped LaMnO3. Issue 8 (12th May 2014) - Liu, Qinyuan; Bhattacharya, Sudip; Helmick, Lam; Donegan, Sean P.; Rollett, Anthony D.; Rohrer, Gregory S.; Salvador, Paul A.; Blendell, J.
<x xml:space="preserve">Abstract</x> Grain‐boundary plane distributions (GBPDs), grain size distribution (GSDs), and upper tail departure from log‐normal GSDs were quantified in dense and porous La0.8Sr0.2MnO3 samples to understand expected microstructures in solid oxide fuel cells. Samples were sintered at 1450°C for 4 h and then annealed between 800°C and 1450°C. The GBPDs and normalized GSDs reached steady state during sintering and little variation occurred during annealing. The GBPDs were nearly isotropic, with the relative areas of {001} planes being slightly higher than random (and the relative areas of {111} planes being less than random). The porous sample had an almost identical GBPD, whereas the almost isotropic pore boundary plane distribution was essentially opposite to the GBPD. The upper tails of the experimental GSDs, and several theoretical distributions, were characterized using peaks‐over‐threshold analysis. Dense samples, and all normal grain growth models, exhibit lower frequencies of large grains in the upper tail than would a log‐normal distribution, and the experimental distributions are similar to the Mullins distribution. Porous samples, however, have an anomalous increased frequency of large grains in the upper tail, as compared to all the model distributions, even though other metrics of the microstructure indicate the dense and porous systems are similar.